Impact of Attendance on Academic Performance in Prenursing Students. Issue 4 (July 2016) - Branson, Marietta; Loftin, Collette; Hadley, Lance; Hartin, Vicki; Devkota, Shravan
Abstract : A descriptive-correlational design was used to explore the relationship between attendance and course grade in a prenursing course. Findings revealed that attendance was positively associated with final course grades ( r 443 = 0.54, P < .001). Traditional students attended a significantly higher percentage of classes than their nontraditional counterparts. These findings support the long-held belief by nursing faculty that attendance positively impacts course outcomes.